2015
DOI: 10.1089/met.2014.0158
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Worse Metabolic Control and Increased Thyroid Volume and Nodular Disease in Elderly Adults with Metabolic Syndrome

Abstract: In elderly patients with metabolic syndrome, worse metabolic control, represented by higher HbA1c levels, was found associated to increased prevalence of thyroid nodules and larger thyroid volume. Moreover, within the whole metabolic syndrome group, patients with T2DM had the largest thyroid volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 23 publications
2
40
1
2
Order By: Relevance
“…Kung et al reported that pregnancy was associated with new thyroid nodule formation and an increase in size of preexisting thyroid nodules [35]. Results of the present study showed that female gender is an independent risk factor not only for goiter but also for thyroid nodules, although some authors could not confirm any gender-related associations [9]. …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Kung et al reported that pregnancy was associated with new thyroid nodule formation and an increase in size of preexisting thyroid nodules [35]. Results of the present study showed that female gender is an independent risk factor not only for goiter but also for thyroid nodules, although some authors could not confirm any gender-related associations [9]. …”
Section: Discussioncontrasting
confidence: 75%
“…Women are more likely to have thyroid disorders, including goiter and thyroid nodules, although some authors could not confirm any gender-related associations [9, 10]. Association of thyroid functional and morphological changes with individual risk factors, especially with smoking habits, has been investigated previously.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective and retrospective studies showed that patients with prediabetes and type 2 diabetes mellitus (T 2 DM) had a significantly increased thyroid volume and a higher prevalence of incident goiter and nodules. Furthermore, diabetic patients treated with metformin had a smaller thyroid volume and a lower risk for the formation of thyroid nodules when compared with controls (Anil et al 2013, Ittermann et al 2013, Blanc et al 2015. These results suggested that metformin exerts an anti-proliferative activity, providing a rationale for an innovative therapy of thyroid proliferative diseases with metformin.…”
Section: Introductionmentioning
confidence: 82%
“…As stated previously, hyperinsulinemia in patients with T 2 DM and/or prediabetes is associated with a higher incidence of benign and malignant tumors. A recent cross-sectional study also found a significant correlation between glycated hemoglobin and thyroid volume or the number of nodules (Blanc et al 2015). Therefore, as an effective insulin-sensitizing drug, metformin may play a significant role in the adjuvant therapy of proliferative disease.…”
Section: Metformin and Ir In Thyroid Nodulesmentioning
confidence: 93%
“…Studies have found that type 2 diabetes in particular is closely related to the development of thyroid nodules. The incidence of thyroid nodules is signi cantly higher in patients with diabetes than in patients without diabetes (9), and thyroid cancer prevalence is higher in patients with glucose metabolism disorders, which are considered a risk factor for thyroid cancer (10,11) .…”
Section: Introductionmentioning
confidence: 99%